Sulfate-reducing bacteria metabolite detection using GC-MS - Nawawi, M.F. (Penerbit Universiti Kebangsaan Malaysia, 2014)
This research was conducted to investigate and compare the various metabolite, produced from the metabolism of two different SRB strain, that were involved in the biocorrosion process. Stainless steel coupons were immersed in two strains of sulfatereducing bacteria, A1H1 and EB3 (designated as SRB1 and SRB2 repectively) were isolated from Port Dickson marine vicinity that were grown in VMNI medium. The immersion period were set for eight days. Analysis of Gas Chromatography-Mass Spectrometry (GC-MS) was conducted using –trimethylsilyl (TMS) of N-methyl-N-trimethylsilylfluoracetamide (MSTFA). The data were than analyzed using Partial Least Squares Discriminant Analysis (PLS-DA) method to discriminate the unique metabolite according to each strain. The result showed that SRB1 generates less metabolite but high in concentration. Meanwhile, SRB2 shows a variety production of metabolites but less in concentration. Both strains share the same metabolism in the production of nitrogen based substance and production of norvaline and pentanoic acid. SRB1 shows a very distinct feature as the production of ribitol was spotted in its metabolism where it is usually associated with growth. SRB2 showed a very close usage of sulphur by production of methionine. These results suggest that different SRB strain produced different number and type of metabolites in the biocorrosion process.